Analysis of the Readiness of School Health Facilities and First Aid for Accidents in the Implementation of the Disaster-Resilient Schools Program in Malang City, Indonesia - Suryanto Eko Agung Nugroho; Antonius Freddy; Ari Prasetyadjati; Aurick Yudha Nagara; Dewi Puspitasari; Unggul Pribadi; Thoriq Muthohari (Advances in Healthcare Research, 2026)
Purpose: This study aims to map the availability of School Health Services (UKS) facilities and the completeness of First Aid kits at partner schools in the Disaster-Resilient Schools program in Malang City, Indonesia. Research Method: This study employed a descriptive cross-sectional design. Data were collected through observations conducted in November 2023 at four schools selected through purposive sampling, using a checklist that included 31 items related to school health unit (UKS) facilities and 21 items related to first aid supplies. The data were analyzed using frequencies and percentages. Results and Discussion: The aggregate proportion of available school health facilities reached 72.58%. Bathrooms/toilets were found in only one school (25%), while stretchers were found in two schools (50%). The aggregate proportion of first-aid kit supplies reached 36.90%. Eye-wash cups and 100 mL vials of distilled water were not found in any of the schools. The results only describe the presence of items, not their functionality, adequacy, accessibility, or disaster preparedness. Implications: Schools need to update their inventory and periodically check the condition and expiration dates of their supplies. Originality: This study presents a contextual mapping of school health units (UKS) and first aid supplies at four partner schools in Malang City, Indonesia.